PRAKTIK PERLOMBAAN KICAU BURUNG DENGAN MERGER HADIAH DAN SINKRONISASI BIAYA TIKET PENDAFTARAN DALAM PERSPEKTIF HUKUM ISLAM (STUDI KASUS DI LAPANGAN ALAM PESONA TEBAS KUALA) - Dian Fariani; Deni Irawan (Pascasarjana Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2020)
The competition in Arabic is called musabaqah, the competition is prescribed because it is a commendable sport. The practice of the bird chirping competition is still vague about the law, especially in this competition that prepares prizes, not even one prize but various kinds of prizes from several parties, with a registration ticket fee which makes it prone to maysir elements in it. The focus of the problem. How is the law of gifts in Islam? How is the law using these gifts? As well as synchronizing registration ticket costs with these prizes. This research method uses an empirical sociological approach. The results of this research are the practice of bird chirping competition with merger prizes and synchronization of registration ticket costs in the perspective of Islamic law (case study at Alam Pesona Tebas Kuala Field), namely: The practice of bird chirping competition with merger prizes and synchronization of registration ticket costs at Alam Pesona Field. Tebas Kuala is a gathering place, hobbies, entertainment facilities as well as prize competitions that prepare various kinds of prizes from several parties that can be obtained by winners and lucky participants on the condition that they register and buy race tickets from the committee when they want to participate in the competition. 2. The practice of bird chirping competition with merger prizes and synchronization of registration ticket fees at Alam Pesona Tebas Kuala Field is not in accordance with Islamic law or Islamic economic principles, where there is still an element of maysir (gambling) in the competition. And the law of prizes obtained by winners or lucky participants in the competition is a syubhat or makruh gift to use. Makruh is something that is recommended by the Shari'a to leave it, if it is abandoned, it will be rewarded and if it is done it will not be sinful.